PERCEIVED RISK AND ABILITIES FOR HEALTH PRACTICES RELATED TO PREVENTION OF TYPE II DIABETES MELLITUS AMONG POSTNATAL MOTHERS WITH GESTATIONAL DIABETES MELLITUS - Bhasy, Bency; Varghese, Linda; Krishnan, Aswathy; Viswanath, Lekha (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: The study is aimed to assess the perceived risk and abilities for health practices related to prevention of Type II diabetes mellitus (DM) among postnatal mothers with gestational DM (GDM). Methods: This is a descriptive study involving 60 postnatal mothers at Amrita Institute of Medical Sciences, Kochi. Non-probability convenience sampling technique was used for the study, data collected through semi-structured questionnaire, risk perception survey for developing diabetes is used to assess the perceived risks and self-rated abilities for health practice scale is used to assess abilities for health practices. Result: Most of the postnatal mothers 55% with GDM had an average personal control and 53% of postnatal mother with GDM were high optimistic that they will not develop Type II DM. In case of diabetes risk knowledge, more than half of the mothers 54% with GDM had average perception. Based on health practices, majority of the postnatal mothers 63 % with GDM have average abilities for health practices related to prevention of Type II DM. Conclusion: Strategies should be designed to care for the postnatal mothers with GDM such as early detection and postpartum screening are mandatory to detect future DM. Â